Polarization in social movements on Twitter - Castillo-de-Mesa, Joaquín (My University, 2019)
Online social networks have become a parallel universe of socialization from which interactive dynamics are generated until recently unknown. From this framework of online communication, different social movements have reached a greater boom and spread. On Twitter these social movements have as a characteristic feature a hashtag (#) that allows cross-cutting the conversation. Although it has become an instrument that makes it possible to agglutinate the conversation in a massive way, we are also emerging voices that warn of the growing manipulation around these forms of socialization. Social workers must pay attention and investigate these means of digital activism in order to understand and avoid these possible manipulations. In this communication we analyze in a longitudinal way different social movements on Twitter. To this end, social movements that have emerged during the last year about phenomena related to the empowerment of women (#metoo, #yositecreo, etc ...), cooperation against natural disasters (#mallorca) and social demands (# pensions). To identify leaderships, detect communities and measure social distances, social network analysis has been used as well as certain algorithms. For the analysis of the conversations, language analysis techniques have been used to optimize the combination of the most common words, giving rise to conversation patterns around certain force ideas.
Online social networks have become a parallel universe of socialization from which interactive dynamics are generated until recently unknown. From this framework of online communication, different social movements have reached a greater boom and spread. On Twitter these social movements have as a characteristic feature a hashtag (#) that allows cross-cutting the conversation. Although it has become an instrument that makes it possible to agglutinate the conversation in a massive way, we are also emerging voices that warn of the growing manipulation around these forms of socialization. Social workers must pay attention and investigate these means of digital activism in order to understand and avoid these possible manipulations. In this communication we analyze in a longitudinal way different social movements on Twitter. To this end, social movements that have emerged during the last year about phenomena related to the empowerment of women (#metoo, #yositecreo, etc ...), cooperation against natural disasters (#mallorca) and social demands (# pensions). To identify leaderships, detect communities and measure social distances, social network analysis has been used as well as certain algorithms. For the analysis of the conversations, language analysis techniques have been used to optimize the combination of the most common words, giving rise to conversation patterns around certain force ideas. The results achieved show a high level of emotivity in the way of interacting and a significant pattern of polarization in conversations about these movements that is the seed of conflicts and radicalization. The key lies in the way we congregate and converse in networks around those with whom we share our perspectives and opinions about the world. This tendency towards homophily provokes a biased and monolithic vision of reality. In order to counteract these conflicts we must raise the level of self-awareness on the level of homophilia in the way we congregate and converse on online social networks and intervene to increase tolerance for diversity.
Keywords: Movimientos sociales; Twitter; Redes sociales; Homophily; Emotivity; Social movements; Social network analysis; Language Analysis